Microbial feed additive - Alimon, Abdul Razak; Nooraee, Seyed Eeman; Abdullah, Norhani; Ho, Yin Wan (2012)

(untitled)
The invention provides a feed additive containing the microorganism Kluyveromyces marxianus WJ1 wherein the feed additive is useful for improved rumen fermentation in ruminant animals. The present invention also provides the use of Kluyveromyces marxianus WJ1 in improving the digestibility of various plant materials and its possible use of it as a microbial feed additive. The feed additive comprises of Kluyveromyces marxianus WJ1, metabolites, yeast, peptone, dextrose, skimmed milk, trehalose and monosodium glutamate and the feed additive contains at least 109 cfu/g of Kluyveromyces marxianus WJ1. The feed additive is further comprised of at least 1.25% w/v of the combination of skimmed milk, trehalose and monosodium glutamate. The feed additive is added into a ruminant feed at a ratio of one gram per animal per day for a significant improvement on rumen fermentation.